Hashtag blessed: Negotiating Online Identity Positions - SAQUETON, GRACE M. (Philippine Humanities Review; Vol 22 No 1 (2020), 2021)
Social media offers mechanisms that “facilitate self-presentation.” These mechanisms include the profile, likes, hashtags, retweets, and other multimedia capabilities (Papacharissi Through these mechanisms individual and collective identities may be simultaneously presented and promoted (304-305). In this paper, I look into the possible role/s that #blessed play/s in identity construction and self presentation. I examine different contexts in which #blessed is used in order to explain the complex interplay among the hashtag, the context, and the identity construction at play. I locate #blessed in the conversation that hashtag discourse on social media has become a linguistic marker that can be used in different communicative functions such as establishing solidarity and online fellowship (Zappavigna 276), a strategy that negotiates between self-praise and positive self presentation (Matley 30), and as a semiotic resource of meaning-making practices (Zappavigna 285). I employ Bucholtz and Hall’s approach to sociocultural linguistics specifically in highlighting the multi-faceted and dynamic nature of identity. By examining ten Facebook posts (caption, photo, and the function of #blessed and other hashtags used), I argue that online identity construction in light of new meaning making practices on social media further re/define identity as dynamic and fragmented entities that continuously acquire and deploy new social meanings as they shape and are re/shaped by different social realities.